The Influence of Migration Timing and Local Conditions on Reproductive Timing in Arctic‐Breeding Birds - W. B. English; B. Lagassé; S. Brown; M. Boldenow; J. Burger; B. Casler; A. D. Dey; S. Feigin; S. Freeman; H. R. Gates; K. E. Iaquinto; S. Koch; et al. (Ecology and Evolution, 2025)
ABSTRACT For birds breeding in the Arctic, nest success is affected by the timing of nest initiation, which is partially determined by local conditions such as snow cover. However, conditions during the non‐breeding season can carry over to affect the timing of breeding. We used tracking and breeding data from 248 individuals of 8 species and subspecies of Arctic‐breeding shorebirds to estimate how the timing of nest initiation is related to local conditions like snowmelt phenology versus prior conditions, measured by the timing and speed of migration. Using path analysis, our global model showed that local and prior conditions have similar effect sizes (Standardised Path Coefficients ± SE of 0.44 ± 0.07 and 0.43 ± 0.07 for snowmelt and arrival timing, respectively), suggesting that both influence the timing of breeding and therefore potentially reproductive output. However, the importance of each variable varied across species. Individuals that arrived later to the breeding grounds did not leave the wintering grounds later, but instead took longer to migrate, potentially reflecting differences in flight speed or time spent at stopover sites. We hypothesise that this may be due to reduced habitat quality at some stopover sites or an inability to adjust their departure timing or migration speed to match the advancing spring phenology in the North. Individuals that migrated longer distances also arrived and nested later. Our results highlight the benefits and potential conservation implications of using a full annual cycle approach to assess the factors influencing reproductive timing of birds.